Soeharto Bukan Dilengserkan Melainkan Mundur: Narasi dalam Pembelajaran Sejarah Indonesia Kelas XII - Farah Febrivi Sianipar; Helrima Sari Siregar; Ivan Fadhillah M.R; Michael Martius Sigalingging (Universitas Hamzanwadi, 2022)
This study aims to describe Soeharto's resignation as president, which is often misunderstood as a resignation. The narrative is also obtained in discussions and discussions on Basic Competencies, namely, Analyzing the development of the political and economic life of the Indonesian nation in the early days of the Reformation in the subject of Indonesian History class XII. This study uses descriptive qualitative research methods. Data collection is done by literature study and document analysis. The results of the study show that President Soeharto was not deposed but resigned by looking at the aspects of formal legality and historical events. Of course, there is tremendous pressure and demand from students, political leaders and the public for President Soeharto to step down from being president of the Republic of Indonesia. Soeharto's resignation can be used as enrichment material, especially in the New Order and Reform class XII material. So that students are expected to be able to think critically and analyze the dynamics of government, the transition of power and the laws regarding the position and resignation of the Indonesian president.